INNOVATIONS IN PROFESSIONAL TRAINING OF HOSPITALITY INDUSTRY EMPLOYEES IN UKRAINE - Gorodianska , Larysa Volodymyrivna; Nazarova , Violetta (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article reveals the influence of innovative training methods on increasing the competitiveness of Ukrainian specialists on the domestic and international labor markets and on the growth of the quality of services in the field of hospitality in Ukraine. General competences acquired by an individual in the process of professional training affect a person’s ability to generate labor income. The appropriate level of renewal of the professional qualities (intellectual potential) of the staff ensures the possibility of implementing innovative development of the enterprise and increasing income.